2014
DOI: 10.1017/s1041610214002385
|View full text |Cite
|
Sign up to set email alerts
|

Caring for caregivers after a stroke

Abstract: Stroke usually occurs in the latter years of life, is sudden and all too often unexpected and unforgiving. When non-fatal, stroke, the second leading cause of disability after dementia, is nearly always disabling (World Health Organization (WHO), 2011). Due to common ensuing physical and cognitive impairments, many stroke survivors are unable to care for themselves in the following weeks, months, and possibly years (Lutz et al., 2011). Thus, the caregiver role is instant and often long-term with no or very lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Our finding that use was generally lower in higher ages (Tables 2 and 3 ) is in accordance with studies from Norway [ 41 ] and other countries [ 7 , 10 , 12 , 42 , 43 ]. It is consistently reported that older adults (55–65 years and over) of both genders are less likely than younger and middle aged to perceive a need for care, to receive referrals from primary care, and to use specialist psychiatric services [ 10 , 43 ]. In older adults visits to the GP for mental health problems seem to be more common than specialist visits [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that use was generally lower in higher ages (Tables 2 and 3 ) is in accordance with studies from Norway [ 41 ] and other countries [ 7 , 10 , 12 , 42 , 43 ]. It is consistently reported that older adults (55–65 years and over) of both genders are less likely than younger and middle aged to perceive a need for care, to receive referrals from primary care, and to use specialist psychiatric services [ 10 , 43 ]. In older adults visits to the GP for mental health problems seem to be more common than specialist visits [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…With the intention of enhancing self-efficacy, self-management, care co-ordination and quality of life, the OHP has been adapted within the broader context of chronic disease. Thus, in the current series of trials our OHP is used to implement this therapeutic framework to enable clinicians and consumers to work systematically towards the achievement of optimal psychosocial health outcomes within mainstream health services [ 23 ]. The self-management foundations of the OHP are particularly relevant for adults affected by stroke and their carers who face the daily challenge of managing various and often simultaneous aspects of their disease such as managing multiple medications, cognitive training, ongoing appointments, and physiotherapy as well as coping with the emotional impact of stroke and their care regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Leaving the exposure to solvents as a causal explanation for the neuropsychological impairment of CSE-patients out of consideration, one could state that the CSE-patients identified at first diagnosis are in fact patients with non-amnestic mild cognitive impairment (MCI) (Petersen 2016 ; Gerstenecker and Mast 2014 ). Mild cognitive impairment is found in the aging population.…”
Section: Discussionmentioning
confidence: 99%